Towards sustainable polymeric nano-carriers and surfactants: facile low temperature enzymatic synthesis of bio-based amphiphilic copolymers in scCO2. Issue 11 (26th February 2016) - Curia, S.; Howdle, S. M.
Abstract : We demonstrate that useful bio-based amphiphilic polymers can be produced enzymatically at a mild temperature, in a solvent-free system and using renewably sourced monomers, by exploiting the unique properties of supercritical CO2 (scCO2 ). Abstract : We demonstrate that useful bio-based amphiphilic polymers can be produced enzymatically at a mild temperature, in a solvent-free system and using renewably sourced monomers, by exploiting the unique properties of supercritical CO2 (scCO2 ). We present the use of a novel near-ambient temperature approach to prepare renewable amphiphilic ABA copolymers in scCO2 . Bio-based commercially available monomers have been polymerised to prepare chains with targeted molecular weight. The amphiphilic materials were prepared by end-capping the synthesised polymers with methoxy poly(ethylene glycol) (MPEG) chains in a one-pot high pressure reaction utilising Candida Antarctica Lipase B (CaLB) as a catalyst at a temperature as low as 35 °C. The block copolymers are characterised by 1 H-NMR, GPC and DSC in order to carefully assess their structural and thermal properties. These polymers form self-assembled aggregates in aqueous environment and these nanostructures are studied through DLS, TEM and UV-Vis. Highly hydrophobic Coumarin-6 was used as a model to prove dispersion in water of lipophilic molecules. Maximum bubble pressure tests demonstrate the reduction in surface tension of these polymers and comparisons are made directly to commercial polymeric non-ionic surfactants.